A new family of EAQMDS codes constructed from constacyclic codes - Chen, Xiaojing (2022)
In this paper, a family of new entanglement-assisted quantum error-correcting codes (EAQECCs) is constructed from constacyclic codes with length n=q2+1a by giving a new method to select defining sets, where a= m2+ 1 , m> 2 is even and q is an odd prime power with a∣ (q± m). It is worth pointing out that those EAQECCs are entanglement-assisted quantum maximum distance separable (EAQMDS) codes when d≤n+22. All of them are new in the sense that their parameters are not covered by the previously known ones. Moreover, they have minimum distance larger than q+ 1. Compared with the codes with the same length listed in Table 1, our codes have larger minimum distance.